2012
DOI: 10.1007/s11746-012-2160-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a New Type of Polyamidoamine and Its Application for Soy Flour‐Based Adhesives

Abstract: The most commonly used curing agents for soybased adhesives are polyamines, which have the problem of low solid content and/or high viscosity. To overcome this problem, a new type of polyamidoamine (PADA) resin was synthesized and applied to soy flour-based adhesives to improve their water resistance. The PADA solution obtained had a high solid content of 50 wt% and low viscosity of 270 cP. The optimum weight ratio of soy flour/ PADA/maleic anhydride to prepare adhesive was 40/7/1.68. The wet strength of plywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…These microstructural features of unbonded surfaces of the four wood species in Figure 2 were similar to those of pine, birch, poplar, and walnut reported earlier. [12,13,22] As per the mechanism proposed by Gent and Li [23], we believed that the high roughness on the unbonded Douglas fir wood surface along with tipping and cracking characteristics enhanced mechanical interlocking between the wood fibers and the adhesive slurry which contributed to the highest wood adhesion that we observed. The SEM image of the bonded Douglas fir wood further confirmed this by the observed fiber splitting features of the pulled-off surface.…”
Section: Discussionsupporting
confidence: 71%
“…These microstructural features of unbonded surfaces of the four wood species in Figure 2 were similar to those of pine, birch, poplar, and walnut reported earlier. [12,13,22] As per the mechanism proposed by Gent and Li [23], we believed that the high roughness on the unbonded Douglas fir wood surface along with tipping and cracking characteristics enhanced mechanical interlocking between the wood fibers and the adhesive slurry which contributed to the highest wood adhesion that we observed. The SEM image of the bonded Douglas fir wood further confirmed this by the observed fiber splitting features of the pulled-off surface.…”
Section: Discussionsupporting
confidence: 71%
“…Although this approach is most widely used (e.g., 4,6,9,11 ), more complicated or multiple overlapped wood specimens have also be used in the adhesive tests (e.g., two 2-layer joints with three wood strips 7,22 , and three 3-layer joints with three wood strips) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that a polyamine solution which had a solid content of 40-60% and a viscosity of less than 600 cP was preferable to prepare soy-based adhesives [32]. To solve the problems of low-solid content and high viscosity of curing agents, our group synthesized a new type of polyamidoamine (PADA) resin [34] for producing soy flour-based adhesives ( Figure 4). The obtained PADA solution had high-solid content of 50 wt% and low viscosity of 270 cP.…”
Section: Adhesives -Applications and Propertiesmentioning
confidence: 99%